PENGATURAN FUNGSI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DALAM PELAYANAN ADMINISTRASI KEPENDUDUKAN MENGENAI KEPENGURUSAN KARTU TANDA PENDUDUK DI KABUPATEN BELU - Adoe, Jovanka Piterzon; Stefanus, Kotan Y; Lamataro, Cyrilius W. T (Petitum Law Journal, 2024)
Population administration is a series of activities carried out by the government in organizing and regulating population documents and data through population registration, civil registration, management of Population Administration information and utilization of the results for public services and other sectors. The main points in this problem are (1) How is the regulation of the function of the Population and Civil Registration Service in population administration services in Belu Regency? and (2) What are the inhibiting factors in the implementation of the function of the Population and Civil Registration Service in population administration services in Belu Regency? This study uses a normative legal and empirical legal approach. Primary data were collected through interviews, while secondary data were obtained from laws and regulations, legal literature, and related documents. The results of the study found that: (1) The arrangement of the functions of the Disdukcapil of Belu Regency has been carried out in accordance with applicable regulations, but there are several inhibiting factors that affect the effectiveness of its services. (2) These factors include the lack of public awareness of the importance of population documents, limited facilities and infrastructure, and the lack of trained human resources.